PENDISTRIBUSIAN BERAS MISKIN (RASKIN) DI KELURAHAN DELIMA KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2016 - Noverdi Saputra; Erman M M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Based on Law No.14 of 2015 on APBN 2016, food subsidies have been set especially for Raskin 2016, which is 15.53 million RTS and 15Kg / month allocation for 12 months at a price of Rp.1,600 / kg at the Distribution Point. Since the food crisis of 1998, the Government has consistently paid great attention to the fulfillment of people's food rights through Special Market Operations (OPK). In contrast to previous food subsidies, OPK provides targeted rice subsidies to poor households and food insecurity.The distribution of the Raskin Program to kelurahan delima has been started since several years ago. The objective of the Raskin Program is to reduce the burden of Expenditure of the Target Household or Rumah Tangga Sasaran (RTS) through the fulfillment of some basic food needs in the form of rice. The target is to reduce the expenditure burden of Target Household in fulfilling the requirement of rice food through the distribution of subsidized rice as much as 15 Kg / RTS / month with the price of Rp.1.600, - / kg at the Distribution Point.The problem of raskin in the kelurahan Delima is the uneven distribution of tasks in each work unit. Where still encountered officers or employees of the Village who do the dualization of work. Lack of socialization to the community related to the recipient and management of Raskin Program. Therefore, many people who do not know what the criteria are classified as Raskin recipients and how the Raskin program management procedures.The concept of theory that the writer uses is the theory of distribution. Broadly speaking, distribution can be interpreted as a marketing activity that seeks to smoothen and facilitate the delivery of goods and services from producers to consumers. therefore, it use in accordance with the required (type, price, place and time required).The result of the research in kelurahan delima related to the distribution of raskin is the subdistrict still has many obstacles where some problems arise is such as the absence of renewal of data of raskin recipients from 2014 and it makes polemic among the society. Moreover, the data until 2016 is still not updated by the sub-district. While Kelurahan Delima is the subdistrict that has smallest number of Poor household or Rumah Tangga Miskin (RTM) compared to other subdistrict.Keywords : distribution, rice for poor (raskin)